SPEECH ACTS AND FUNCTIONS OF EXPRESSIVE SPEECH OF POLISH BIPA LEARNERS AT UPT BAHASA UNS - Siagian, Evrin Septya Lilasa; Suwandi, Sarwiji; Andayani, Andayani (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2018)
This study aimed to describe the use of speech acts in the form of locutionary acts, illocutionary acts, perlocutionary acts, and expressive speech acts used by foreign learners in the learning process ofÂ  Indonesian Language for Foreigners (BIPA). This research used descriptive qualitative method. The subject of this research was a Polish student who had been joining Darmasiswa Program at UPT Bahasa, Universitas Sebelas Maret. The technique of collecting data was by using free-listening-participating-speaking (SBLC). The technique of analyzing data was by using the interactive model. The interactive model used in this research was the extralingual interactive model. The results showed that there were types of locutionary acts, illocutionary acts, perlocutionary acts, and functions of expressive speech acts consisting of congratulating, expressing gratitude, criticizing, complaining, giving compliment, apologizing, offering and motivating.Keywords/phrases: speech acts, expressive speech acts, BIPA TINDAK TUTUR DAN FUNGSI TUTURAN EKSPRESIF PEMELAJAR BIPA ASAL POLANDIA DI UPT BAHASA UNSAbstrakPenelitian ini bertujuan untuk mendeskripsikan penggunaan tindak tutur berupa tindak tutur lokusi, ilokusi, perlokusi, dan tuturan ekspresif yang digunakan pemelajar asing dalam proses pembelajaran Bahasa Indonesia bagi Penutur Asing (BIPA). Metode yang digunakan adalah deskriptif kualitatif. Subjek dalam penelitian ini adalah mahasiswa asing asal Polandia yang sedang mengikuti program Darmasiswa di UPT Bahasa Universitas Sebelas Maret. Teknik pengumpulan data adalah teknik perekaman dengan metode simak bebas libat cakap (SBLC). Analisis data menggunakan metode padan ekstralingual. Hasil penelitian menunjukkan bahwa terdapat jenis-jenis tindak tutur lokusi, ilokusi, perlokusi dan fungsi tuturan ekspresifnya yang terdiri dari tuturan ekspresif mengucapkan selamat, terima kasih, mengkritik, mengeluh, memuji, meminta maaf, menawarkan, serta memotivasi.Kata Kunci/frase: tindak tutur, tuturan ekspresif, BIPA Â